Program Proposals for Feed Grain Producers. hearings before the United States House Committee on Agriculture, Subcommittee on Livestock and Feed Grains, Eighty-Fifth Congress, second session, on Apr. 16, 17, 1958. (U.S. Congressional Hearings., 1958)
Committee Serial NN.